Ammoniacal Cyanide Leaching Of Complex Gold Ore - Merdan, Fathin Atiqa (Universiti Sains Malaysia, 2022)
The gold ore samples obtained in this study were exposed to ammonia cyanidationleaching at different levels of ammonia (NH3) and sodium cyanide (NaCN) reagents in gold and copper extractors. Mineral characterization of gold ore samples was carried out to identify mineral correlation, mineral composition, and mineral phase through XRD and XRF analysis. The 'bottle roll' test method is used to obtain basic information about the solubility of certain Au-bearing ores. The primary effects and interactions of NH3 and NaCN are shown in the ammonia cyanide system using a 'Full Factorial' experimental design. NH3 and NaCN concentrations have been statistically proven to be the main determinants affecting gold extractability. The amount of gold obtained from the fire test technique is 2.762 mg/L. The largest yield using the ammonia leaching technique to determine free gold in gold ore samples was 2.625 mg/L using 3000 ppm cyanide, and 1000 ppm ammonia. Therefore, it can be concluded that ammonia leaching solvent can increase the release of high gold particles with high consumption of cyanide and ammonia.